Integrasi Manajemen Pendidikan Islam dalam Kurikulum Pondok Pesantren Modern - Rastina; Bahruddin; Anita Diah Kurniawati; Suratman; Akhmad Ramli (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to explore how Islamic education management is integrated into the curriculum of a modern Islamic boarding school, taking a case study at SMP Islam Asqolan Boarding School Samarinda. The research focuses on how the curriculum is planned, implemented, and evaluated by aligning the principles of Islamic education management with the demands of a contemporary curriculum. Using a qualitative approach with a case study design, the data were collected through interviews, field observations, and document analysis. The analysis followed the model of Miles, Huberman, and Saldana, involving stages of data condensation, data display, and conclusion drawing. The findings reveal that the integration of Islamic education management is reflected in a collaboratively structured curriculum, the consistent cultivation of Islamic values in daily learning activities, and an evaluation process aimed at strengthening students’ character and competencies. Overall, the study provides a comprehensive picture of how Islamic education management can be blended into a modern pesantren curriculum, offering a useful reference for curriculum development in similar institutions. This integration underscores the importance of solid educational management as a foundation for improving institutional quality and preparing students to adapt to ongoing changes in the educational landscape.